The role of epithelial mesenchymal transition and resistance to neoadjuvant therapy in locally advanced rectal cancer. (April 2014) - Bhangu, A.; Wood, G.; Brown, G.; Darzi, A.; Tekkis, P.; Goldin, R.
Abstract Aim Nonresponse to neoadjuvant therapy is a significant challenge for clinicians managing solid cancers. This study aimed to determine whether epithelial mesenchymal transition (EMT) was associated with nonresponse to neoadjuvant therapy in patients with locally advanced rectal cancer. Method Representative tissue specimens from the tumour‐invasive front of consecutive patients undergoing resection of rectal cancer from 2009 to 2011 were used. Patients with marked regression to neoadjuvant therapy were classified as responders and the remainder were classified as nonresponders. Markers of EMT included reduced immunohistochemical expression of membranous E‐cadherin, increased nuclear beta‐catenin expression and tumour budding. In‐situ hybridization was used to assess the expression of microRNA‐200c (mir200c), an upstream master‐regulator of EMT. Results Of 103 patients undergoing resection of rectal cancer, 69 received neoadjuvant chemoradiotherapy; 65% of these were nonresponders. Reduced expression of mir200c was significantly associated with a higher T grade. Reduced membranous E‐cadherin, increased nuclear beta‐catenin and tumour budding individually predicted the presence of extramural vascular invasion. Reduced E‐cadherin, nucleic beta‐catenin, reduced expression of mir200c and tumour budding were all significantly associated with nonresponse to neoadjuvant therapy (all P < 0.001). Reduced E‐cadherin and expression of mir200c were both associated with reduced cancer‐specific survival (log‐rank P‐values 0.036 and 0.009, respectively). Conclusion Targeted biomarkers of EMT were associated with nonresponse to neoadjuvant therapy and reduced survival in advanced rectal cancer. EMT may provide a practical clinical biomarker and a novel therapeutic target to improve the proportion of patients who respond to neoadjuvant therapy.